A compact planar inverted‐F antenna with U‐shaped strip for all‐metal‐shell handset application. Issue 5 (24th January 2018) - Han, Chong‐Zhi; Fan, Mo‐Lin; Zhong, Zeng‐Pei; Zeng, Qing‐Fa; Huang, Guan‐Long; Xu, Wei; Yuan, Tao
Abstract: A compact dual‐band planar inverted‐F antenna (PIFA) with U‐shaped strip is proposed in this work for all‐metal‐shell mobile telephone application. As metal‐shell handsets are getting more and more popular nowadays, it raises a big challenge in antenna design as the metal‐shell associated with surrounding electronic components like front‐back‐cameras and telephone receiver would affect the antenna performance. This work provides an optional solution to alleviate this problem, where the metal shell of the handset and a U‐shaped strip are utilized as part of the antenna. The proposed antenna is able to generate radiation at 2.4 GHz for Wi‐Fi application with the help of the metal shell while using the U‐shaped strip can achieve a resonance at 1.575 GHz for GPS application. A prototype has been fabricated to verify the radiation performance in a practical handset test environment.